Review of the Lispe caesia-group (Diptera: Muscidae) from Palaearctic and adjacent regions, with redescriptions and one new synonymy - Zhang, Dong; Ge, Ying-Qiang; Li, Xin-Yu; Liu, Xian-Hui; Zhang, Ming; Wang, Rong-Rong (Zootaxa, 2016)
Species of Lispe caesia-group from Palaearctic and adjacent regions are reviewed. Diagnostic characters of this group are updated. One new synonymy is established: L. frontalis Zielke, 1972, syn. nov. for L. leucocephala Loew, 1856. Key to males of ten species (with two subspecies) from Palaearctic, Oriental and Ethiopian regions is given. Nine species (with two subspecies) are photographed. Six species and one subspecies are redescribed. More detailed ultrastructural or external characters for male swollen hind tarsi and the wing interference patterns are also provided.